Penyuluhan Edukasi tentang Stunting di Puskesmas Duduksampeyan Kabupaten Gresik: Educational Outreach about Stunting at the Panggangsampeyan Community Health Center, Gresik Regency - Aminatus Sadiyah, Siti; Widyowati, Agustin (Chakra Brahmanda Lentera Institute, 2024)
Stunting is a condition in which children experience growth disorders, resulting in height not being appropriate for their age due to malnutrition for a long period of time. Handling this problem requires serious attention from various parties. In addition to affecting physical growth, stunting also makes children more susceptible to diseases and can interfere with their brain development and intelligence. To increase public awareness about stunting, Centing Seni activities in the form of educational counseling were carried out at the Duduksampeyan Health Center, Gresik Regency. The methods used include approaches to community leaders, counseling on stunting prevention, and examination of toddlers. This activity aims to provide clear and useful information to mothers about how to prevent stunting and the importance of adequate nutrition for children. The Centing Seni activity ran successfully and effectively in increasing the knowledge of mothers about stunting. Active community involvement and positive responses to counseling show that these efforts have achieved the desired results. Participants showed a better understanding of stunting prevention and the steps that need to be taken to ensure nutritional adequacy for their children. The contribution of Centing Seni activities is very important in supporting the government's program to reduce the incidence of stunting in Gresik Regency. It is hoped that the knowledge gained from this counseling will be applied in daily life by the community to prevent stunting.